The nutritional status of Orang Asli children after participating in the community feeding program (CFP) in Gua Musang and Jeli, Kelantan - Abdullah, Noor Aida (2021)
Background: Malnutrition is one of the main causes of death and disease among children globally. The economic, social, and medical impacts of malnutrition are serious and long-lasting. It can affect the growth and development of children and had subsequently, chronic diseases in adults. To counteract malnutrition, nutrition programs have been put in place to improve the nutritional well-being of Malaysian children. The Community Feeding Program (CFP), focused specifically on the underprivileged community such as the Orang Asli due to the persistently high prevalence of malnutrition. Objectives: This study aimed to investigate the proportion and factors associated with the successful outcome of the CFP among Orang Asli children in Gua Musang and Jeli, Kelantan. Methodology: A cross-sectional study was conducted involving 175 recipients of Orang Asli children aged between six months to six years old who participated in the CFP in Gua Musang and Jeli, Kelantan. Data were collected from Buku Kanak-Kanak Kekurangan Zat Makanan (BKKKZM) using a proforma. This program involved a combination of three interventions; provision of Ready to Used Therapeutic Food (RUTF), Supplementary Feeding, and Community Health Empowerment Program Result: This study showed an improvement in the nutritional status indicators such as height, weight, height-for-age (stunting), and weight-for-age (underweight) after six months in the program. The proportion of successful outcome of nutritional status increased to 64.0% for underweight and 65.1% for stunting. Factors associated with the underweight successful outcome include location of feeding centres (AOR; 3.34, 95% CI:1.550, 7.180) and percentage of attendance (AOR; 1.058, 95% CI: 1.189, 6.738). While factors associated with the stunting successful outcome include location of feeding centres (AOR; 4.07, 95% CI:1.86, 8.90) and fathers education (AOR; 2.83, 95% CI: 1.03, 1.08). Conclusion: The Community Feeding Program showed the improvement in the nutritional status of Orang Asli children, thus this program should be sustained to increase the success of the program.